The Influence of Fermentation Conditions on the Content of Phenolic Compounds, Anthocyanins and the Spectral Characteristics of Cabernet Sauvignon Wines - Yoncheva, Tatyana (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The wine characteristics have been determined by the variety potential and specificity, but also by the yeast strain carrying out the alcoholic fermentation. Phenolic components and anthocyanins play a significant role in the formation of the organoleptic wine qualities, especially of red wines. The yeast affects the colour of the wine mainly with the extracellular β-glucosidase they produce. The objective of the study was to investigate the influence of the technological factors yeast strain, temperature and inoculum amount of yeast culture on the variation of the total phenolic compounds and anthocyanins during the alcoholic fermentation and on the spectral characteristics of Cabernet Sauvignon wines. The experiment was carried out with grapes of Cabernet Sauvignon variety with sugars content of 23.10 % and titratable acids of 6.15 g/dm3. The alcoholic fermentation was conducted with inoculum amount of yeast culture 2, 3 and 4 % of the strains Bordeaux and 8-11 of Saccharomyces cerevisiae species. The fermentation temperature was 20, 24 and 28 оС. The course of the process was followed by the variation in the dry matter, measured daily with the Abbe refractometer. The dynamics of the total phenolic compounds and the anthocyanins during the fermentation was determined by measuring on 1st, 5th, 10th and 20th day. After the alcoholic and the malolactic fermentations in the experimental wines were also analyzed the content of flavonoid phenolic compounds, non-flavonoid phenolic compounds and their spectral characteristics. The results demonstrated that under the experimental conditions both strains Bordeaux and 8-11 exhibited the best fermentation activity at 28 °C. The temperature factor had a stronger impact on the variations of total phenolic compounds and anthocyanins in the course of the alcoholic fermentation. The quantitative maximum of both indicators was recorded on the 5th day of the process. In the experimental wines, the variants fermented under the conditions of 28 °C/4 % contained more total phenolic compounds, anthocyanins, flavonoid phenolic compounds and non-flavonoid phenolic compounds. The red colour ratio also was the highest. The wines of 8-11 strain were distinguished by a higher content of total phenolic compounds, anthocyanins and, respectively a more intense colour.